Strategy of Monitoring, Tracing and Evaluation - SGP - Sector Education (2013)
Impact analysis obtained by the Monitoring Strategy, Monitoring and Evaluation of the General Resources Sharing System in the Educational Sector posed by Decree 028 of 2008.